2020
DOI: 10.1177/0093854820932959
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Pretrial Risk Assessments: A Systematic Review of the Literature

Abstract: Bail reform is sweeping the nation and many jurisdictions are looking to pretrial risk assessment as one potential strategy to support these efforts. This article summarizes the findings of a systematic review of research examining the predictive validity of pretrial risk assessments. We reviewed 11 studies (13 publications) examining the predictive validity of six pretrial risk assessment instruments reported in the gray and peer-reviewed literature as of December, 2018. Findings typically show good to excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 52 publications
2
78
1
Order By: Relevance
“…Total scores ranging from 0 to 9 classify individuals into three risk categories: Low (0-2), Moderate (3-5), and High (6+). IRAS-PAT assessments have produced predictive accuracy similar to other pretrial risk assessments (Desmarais et al, 2020;Lowder et al, 2020b). Supervision level (Low, Moderate, High) measured the judge-ordered supervision level.…”
Section: Independent Variables Independent Variables Included Iras-pat Risk Levelmentioning
confidence: 80%
See 1 more Smart Citation
“…Total scores ranging from 0 to 9 classify individuals into three risk categories: Low (0-2), Moderate (3-5), and High (6+). IRAS-PAT assessments have produced predictive accuracy similar to other pretrial risk assessments (Desmarais et al, 2020;Lowder et al, 2020b). Supervision level (Low, Moderate, High) measured the judge-ordered supervision level.…”
Section: Independent Variables Independent Variables Included Iras-pat Risk Levelmentioning
confidence: 80%
“…To date, there are a growing number of studies focused on evaluating the accuracy and effectiveness of pretrial risk assessments as an alternative to money bail (Desmarais et al, 2020;Lowder et al, 2020a;Stevenson, 2018). However, there are fewer contemporary studies examining the use of risk assessment-informed pretrial supervision, despite nearly half of local jurisdictions reporting use of pretrial supervision and a similar proportion reporting use of pretrial risk assessments (Lattimore et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most reviews of pretrial risk assessment instruments are completed within local agencies; thus, there are few peer-reviewed studies examining their predictive validity (Desmarais et al, 2021). Most recently, DeMichele et al (2020) examined the PSA on a statewide data set collected in Kentucky ( N = 164,597) between July 1, 2013, and December 30, 2014.…”
Section: The Utility Of Pretrial Risk Assessment Instrumentsmentioning
confidence: 99%
“…Individuals who scored a 1 failed to appear for court or were arrested 13% of the time, followed by 29% for those who scored a 2, 42% for those who scored a 3, and 67% for those who scored a 4. Desmarais et al (2021) examined the results of 10 pretrial risk assessment instruments and found that the AUC scores typically produced fair to medium effects (Rice & Harris, 2005). Furthermore, all PSA-specific peer-reviewed literature to date has examined Kentucky data and has been funded by the creators of the PSA—Arnold Ventures (Desmarais et al, 2021); thus, the need to rigorously examine PSA data from other jurisdictions.…”
Section: The Utility Of Pretrial Risk Assessment Instrumentsmentioning
confidence: 99%
“…Specifically, pretrial risk assessment instruments provide structure to reduce bias and promote a transparent and evidencebased approach for estimating the likelihood someone will fail to appear in court or be rearrested during the pretrial period. Pretrial risk assessment instruments are typically quite short, completed through record review and/or in person interview, and rely on an algorithmic approach to combine item ratings into risk scores (Desmarais et al, 2020). Jurisdictions across the United States have incorporated the use of pretrial risk assessment instruments to support bail reform .…”
Section: Implementing Pretrial Risk Assessment Instrumentsmentioning
confidence: 99%